Race‐specific molecular alterations correlate with differential outcomes for black and white endometrioid endometrial cancer patients. Issue 20 (27th June 2017) - Bateman, Nicholas W.; Dubil, Elizabeth A.; Wang, Guisong; Hood, Brian L.; Oliver, Julie M.; Litzi, Tracy A.; Gist, Glenn D.; Mitchell, David A.; Blanton, Brian; Phippen, Neil T.; Tian, Chunqiao; Zahn, Christopher M.; et al.
Abstract : BACKGROUND: The objective of this study was to identify molecular alterations associated with disease outcomes for white and black patients with endometrioid endometrial cancer (EEC). METHODS: EEC samples from black (n = 17) and white patients (n = 13) were analyzed by proteomics (liquid chromatography–tandem mass spectrometry) and transcriptomics (RNA‐seq). Coordinate alterations were validated with RNA‐seq data from black (n = 49) and white patients (n = 216). Concordantly altered candidates were further tested for associations with race‐specific progression‐free survival (PFS) in black (n = 64) or white patients (n = 267) via univariate and multivariate Cox regression modeling and log‐rank testing. RESULTS: Discovery analyses revealed significantly altered candidate proteins and transcripts between black and white patients, suggesting modulation of tumor cell viability in black patients and cell death signaling in black and white patients. Eighty‐nine candidates were validated as altered between these patient cohorts, and a subset significantly correlated with differential PFS. White‐specific PFS candidates included serpin family A member 4 (SERPINA4; hazard ratio [HR], 0.89; Wald P value = .02), integrin subunit α3 (ITGA3; HR, 0.76; P = .03), and Bet1 Golgi vesicular membrane trafficking protein like (BET1L; HR, 0.48; P = .04). Black‐specific PFS candidates included family with sequence similarity 228 member B (FAM228B; HR, 0.13; P = .001) and HEAT repeat containing 6 (HEATR6; HR, 4.94; P = .047). Several candidates were also associated with overall survival (SERPINA4 and ITGA3) as well as PFS independent of disease stage, grade and myometrial invasion (SERPINA4, BET1L and FAM228B). CONCLUSIONS: This study has identified and validated molecular alterations in tumors from black and white EEC patients, including candidates significantly associated with altered disease outcomes within these patient cohorts. Cancer 2017;123:4004‐12 . © 2017 American Cancer Society . Abstract : Disparities in disease outcomes between black and white patients with endometrial cancer may be due in part to inherent differences in the disease biology. This study has identified conserved molecular alterations between black and white patients with endometrioid endometrial cancer correlating with differential disease outcomes, and it provides further insights into the association of race‐specific biology with disease prognosis in patients with endometrial cancer.